2023
DOI: 10.1007/s00109-023-02324-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased Fusobacterium tumoural abundance affects immunogenicity in mucinous colorectal cancer and may be associated with improved clinical outcome

William P. Duggan,
Manuela Salvucci,
Batuhan Kisakol
et al.

Abstract: There is currently an urgent need to identify factors predictive of immunogenicity in colorectal cancer (CRC). Mucinous CRC is a distinct histological subtype of CRC, associated with a poor response to chemotherapy. Recent evidence suggests the commensal facultative anaerobe Fusobacterium may be especially prevalent in mucinous CRC. The objectives of this study were to assess the association of Fusobacterium abundance with immune cell composition and prognosis in mucinous CRC. Our study included two independen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Futhermore, several studies have indicated that Fusobacterium nucleatum ( F. nucleatum ) could promote the occurrence and development of CRC [ 37 40 ], while metformin has been shown to alleviate symptoms and inhibit the formation of intestinal tumors in F. nucleatum -administered APCMin/ + mice [ 28 ]. Additionally, g_Ruminococcus has been increasingly recognized for its connection to metabolic diseases [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Futhermore, several studies have indicated that Fusobacterium nucleatum ( F. nucleatum ) could promote the occurrence and development of CRC [ 37 40 ], while metformin has been shown to alleviate symptoms and inhibit the formation of intestinal tumors in F. nucleatum -administered APCMin/ + mice [ 28 ]. Additionally, g_Ruminococcus has been increasingly recognized for its connection to metabolic diseases [ 41 ].…”
Section: Discussionmentioning
confidence: 99%